Getting to know from our millennials students: different perception of career expectations and career goals / Rina Agustina and Nurhidayati Nurhidayati - Agustina, Rina; Nurhidayati, Nurhidayati (Universiti Teknologi MARA, Perlis, 2021)
Research on career expectations and career goals was becoming a concern for practitioners in the Human Resource Management field. A career is important because it is a need that must be cultivated in an employee, to be able to boost their performance. Meanwhile, based on their characteristics, employees have different views about career expectations and goals. This study aims to analyze career expectations and goals from the perspective of the millennial generation based on gender, achievement and domicile. This study involved 200 students of the final semester at universities in the city of Semarang and measured their perceptions of career expectations as to future employees by using the SPSS Two-Sample Independent Mean Test for the average difference test. By using the average difference test, this study found that perceptions of career expectations differ based on gender and achievement. Implication and future research agenda provided for the direction of future work.